Side branch long lesion with main vessel vulnerable plaques by optical coherence tomography predict target-vessel myocardial infarction after provisional stenting in patients with coronary bifurcation. (25th November 2020) - Chen, S.L
Abstract: Background: Provisional side branch (SB) stenting is correlated with target-vessel myocardial infarction (TVMI) in patients with coronary bifurcation lesions. However, the underlying mechanisms remain unknown. Objectives: We aimed to determine the correlation of SB lesion length with vulnerable plaques using optical coherence tomography (OCT) and TVMI in patients with coronary bifurcation lesions treated by a provisional approach. Methods: A total of 405 patients with 405 bifurcation lesions who underwent pre-PCI OCT imaging of both main vessel (MV) and SB was prospectively enrolled. Patients were defined as Long-SB lesion (SB lesion length ≥10 mm) and Short-SB lesion (SB lesion length <10 mm) groups according to quantitative coronary analysis and were also stratified by the presence of vulnerable plaques based on OCT findings. The primary endpoint was the occurrence of TVMI after provisional stenting at one-year follow-up. Results: 178 (43.9%) patients had long SB lesions. Vulnerable plaques predominantly localized in the main vessel (MV) and more frequently in the Long-SB lesion group (42.7%) compared to 24.2% in the Short-SB lesion group (p<0.001). At one-year follow-up after provisional stenting, there were 31 (8.1%) TVMIs, with 11.8% in the Long-SB lesion group and 4.4% in the Short-SB lesion group (p=0.009), leading to significant difference in target lesion failure between two groups (15.2% vs. 6.6%, p=0.007). The rate of cardiac death, revascularization, and stent thrombosis was comparable between study groups. By multivariate regression analysis, long SB lesion length (p=0.011), presence of vulnerable plaques in the polygon of confluence (p=0.001), and true coronary bifurcation lesions (p=0.004) were three independent factors of TVMI. Conclusions: Long-SB lesion length with MV vulnerable plaques predict increased TVMI after provisional stenting in patients with true coronary bifurcation lesions. Further study is warranted to identify the better stenting techniques for coronary bifurcation lesions with long lesion in the SB Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): NSFC